2013
DOI: 10.3904/kjim.2013.28.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic drainage in patients with inoperable hilar cholangiocarcinoma

Abstract: Hilar cholangiocarcinoma has an extremely poor prognosis and is usually diagnosed at an advanced stage. Palliative management plays an important role in the treatment of patients with inoperable hilar cholangiocarcinoma. Surgical, percutaneous, and endoscopic biliary drainage are three modalities available to resolve obstructive jaundice. Plastic stents were widely used in the past; however, self-expanding metal stents (SEMS) have become popular recently due to their long patency and reduced risk of side branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…It was finally concluded that "Endoscopic-ultrasound-guided hepaticogastrostomy is safe and can be a good palliative option for advanced malignant biliary obstruction because it drains internally and is remote from the tumor site, promoting a long patency period of prosthesis and better quality of life (7)." This observation is concordant with the report from other centers (8,9).…”
supporting
confidence: 64%
“…It was finally concluded that "Endoscopic-ultrasound-guided hepaticogastrostomy is safe and can be a good palliative option for advanced malignant biliary obstruction because it drains internally and is remote from the tumor site, promoting a long patency period of prosthesis and better quality of life (7)." This observation is concordant with the report from other centers (8,9).…”
supporting
confidence: 64%
“…Unfortunately, PSs have a shorter period of patency than SEMSs, and clogging can progress to jaundice and/or cholangitis . PS clogging is thought to be multifactorial and associated with bacterial contamination of undrained bile ducts . PSs may be a viable option for patients with a short life expectancy (usually defined as less than 3 months).…”
Section: Metal Stents Versus Pssmentioning
confidence: 99%
“…10 PS clogging is thought to be multifactorial and associated with bacterial contamination of undrained bile ducts. 9,11,12 PSs may be a viable option for patients with a short life expectancy (usually defined as less than 3 months). The prophylactic administration of antibiotics, the administration of ursodeoxycholic acid, and the utilization of wider PSs have been evaluated as ways of reducing PS clogging, but the benefits have been limited.…”
Section: Metal Stents Versus Pssmentioning
confidence: 99%
See 2 more Smart Citations